International Perspectives on the Legal Framework Governing Prosecutorial Activities - Yevhen Leheza; Oleksii Kalchuk (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
This article seeks to illuminate how prosecutors' offices are legally regulated internationally. Through a comparative analysis of various foreign prosecutors' offices, the study presents information regarding their position within the government, the models they utilise, and their core functions. This allows for understanding the role and evolution of prosecutors' offices in prominent countries today. Germany, for instance, has public prosecutors' offices operating within all levels of its general court system. The Federal Prosecutor General operates under the general oversight of the German Minister of Justice. Meanwhile, the French prosecutor's office is considered part of the executive branch and is subject to the authority of the Ministry of Justice. French prosecutors share a close relationship with the judiciary, undergoing similar training and often transitioning between roles as prosecutors and judges. Latvian law designates the prosecutor's office as a judicial body. This office independently oversees adherence to the law within its defined jurisdiction. The United Kingdom has no specific "public prosecutor's office" or equivalent.Keywords: prosecutor's Office; Organisation of the prosecutor's office; Models of foreign prosecutor’s Offices; Positioning of the Prosecutor's Office; Powers of Foreign Prosecutors